Acoustic metamaterial-enhanced quarter wavelength resonator for noise-to-electrical energy conversion - Eduria, Art Jared Elmundo; Bayantong, Allen Rhay Bagsinao; R. Puno, Jennifer; Chrizelyn E. Añasco, Honey; Jay G. Cabsag, Lesther; A. Cañete, Angelica (MDP Student Conference, 2024)
Amidst the surging global population and industrialization, a pressing demand for electricity emerges, posing environmental challenges. This research endeavors to engineer an energy harvesting device capitalizing on abundant, clean, and renewable ambient energy—specifically, noise energy—for conversion into electrical energy. The proposed Acoustic Metamaterial Coupled Quarter-Wavelength Resonator (AMQR) is a novel energy harvesting mechanism. Utilizing a quarter-wavelength resonator (QR), it concentrates and amplifies incident sound waves onto a piezoelectric plate, optimizing the generation of electrical voltage. Operational parameters are systematically optimized through Design Expert 7.0 software and Central Composite Design of Response Surface Methodology. Results demonstrate that at a 5 cm AMQR distance from the noise source and a 60 mm QR height, the device attains a peak electrical voltage of 120 mV. This underscores the efficiency of the AMQR in harvesting and converting noise/sound energy into electrical energy, offering a promising avenue for sustainable electricity generation from ambient sources.